Evaluating Straddle Carrier Deployment Policies: A Simulation Study for the Piraeus Container Terminal - HADJICONSTANTINOU, Eleni (Institutional Knowledge at Singapore Management University, 2009)
Most container terminals in the world today are operating up to their capacities. In this paper, we have developed a decision support system to optimise yard operations by considering all container flows (import, export and transshipment) through the yard with the view to improving the terminal performance and efficiency. In another paper, we proposed an optimisation model that determines optimal container locations and straddle carrier (SC) movements with the objective of minimising the overall storage and handling cost of containers. In this paper, a discrete event simulation tool for container terminal operations has been developed with three objectives: (i) to validate the operational plan resulting from the optimisation model, (ii) to test the robustness of possible deployment policies for straddle carriers and (iii) to analyse yard resource requirements for future terminal expansion. The model has been applied to the largest container terminal in Greece - the Port of Piraeus and computational results are reported for the case study.